Loss of Malignancy in Mouse Melanoma Cells by Long-Term Impact of Interferon-Beta In Vitro is Associated with N- and VE-Cadherins Suppression without Inhibition of Expression of EMT-Associated Twist and Slug Proteins (Journal of Analytical Oncology, 2014)
Aim: To study the effect of long-term impact of mouse interferon-beta (IFN-b) on the behavior of mouse melanoma cells in vitro and in vivo and the expression of epithelial-mesenchymal transition (EMT) associated proteins. Materials and Methods: Studies were performed on mouse B16 melanoma cells as a tumor model (MM-4 cell line). Immunocytochemical and tumor cell biology approaches have been used in this study. Results: Long-time treatmentof MM-4 melanoma cellswith low-dose IFN-b (1/2 of IC50) leads to change their morphology, significant inhibition of cell growth and plating efficiency, suppression of cell migration and anchorage-independent growth in semisolid agar. Moreover, IFN-modification of melanoma cells is accompanied by the significant suppression of their malignancy in vivo: growth of tumor induced by IFN-treated cells has inhibited on 50% and growth of metastases - on 90%. Also, IFN-modification of MM-4 cells affects on the expression of proteins involved in cell cycle regulation and inhibits expression of some molecules of adhesion (N-, VE-cadherins), but not influence on the expression of EMT-associated Twist and Slug proteins and E-cadherin. Conclusions: Long-term impact of mouse IFN-beta in low dose on melanoma cells in vitro changes their phenotype and inhibits their proliferative potential, signs of malignancy in vitro, tumorigenicity and metastatic ability in vivo. Loss of malignancy is associated with inhibition of N- and VE-cadherins expression, but not associated with the change of expression and subcellular localization of E-cadherin and EMT transcription factors Twist and Slug.